Integrating vosoritide therapy with limb surgery in paediatric patients with achondroplasia: real-life experiences - Anna Elsa Maria Allegri; Maria Francesca Bedeschi; Maria Beatrice Bocchi; Valentina Camurri; Michaela Veronika Gonfiantini; Chiara Leoni; Milena Mariani; Osvaldo Palmacci; Matteo Porro; Simone Riganti; Caterina Tedesco; Berardo Rinaldi; et al. (Orphanet Journal of Rare Diseases)
Abstract Background Achondroplasia is the most common form of disproportionate short stature and can lead to serious medical complications, including foramen magnum and spinal stenosis. Until 2021, there were no precision treatments available, and in some countries, elective surgery was considered a standard approach to increase height, improve body proportions, enhance functionality, and correct deformities in a selected group of patients. Recently, C-type natriuretic peptide (CNP) has been explored as a potential treatment, aiming to counteract the molecular activity driven by FGFR3. Although post-market and real-world data on the drug are still limited, many questions remain about the potential for combining pharmacological and surgical therapies and how this might influence patient outcomes. Concerns have also been raised regarding the potential impact of drugs on bone healing. However, anecdotal evidence from orthopaedic practice suggests that the two ossification processes do not interfere with one another. The aim of this study was to describe the first real-world case series in which vosoritide treatment was integrated with limb surgery in children and adolescents with achondroplasia. Results Sixteen paediatric patients with molecular confirmation of achondroplasia were included in the study. All patients underwent combined vosoritide therapy and limb surgeries (13 for lower limb lengthening and 3 for varus correction through epiphysiodesis).The complementary roles of vosoritide therapy and surgery were highlighted, with treatment outcomes aligning closely with expectations. Conclusion This report provides the first clinical description of the combination of precision therapy with limb surgery in a relatively large multicentre cohort of paediatric patients with achondroplasia. These findings support continued exploration of the integration of different therapeutic approaches.